2021
DOI: 10.1086/712445
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Price Dispersion and Cycles

Abstract: We report a continuous time experiment studying the classic Burdett and Judd (1983) model, whose unique Nash equilibrium (NE) features dispersed prices. Adaptive dynamics predict that the NE is stable for one parameter set we use, and unstable for another parameter set. The empirical price distribution turns out to be close to the NE distribution for the stable parameter set overall, but for the unstable parameter set the empirical distribution skews towards higher prices in its NE support interval.We offer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Since 2010, the convenience of this method has been improved by empirical observations. The cycle is one example of this [7,6,40,37,39,38,32,29,2], and it may become a constitute element in the paradigm's distinct set of concepts. Because a cycle generally exists in mixed-strategy Nash equilibrium behaviours, it is a consequence of the engagement of strategy interactions; moreover, it demonstrates game evolution, and is an exploitable PTDE.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2010, the convenience of this method has been improved by empirical observations. The cycle is one example of this [7,6,40,37,39,38,32,29,2], and it may become a constitute element in the paradigm's distinct set of concepts. Because a cycle generally exists in mixed-strategy Nash equilibrium behaviours, it is a consequence of the engagement of strategy interactions; moreover, it demonstrates game evolution, and is an exploitable PTDE.…”
Section: Discussionmentioning
confidence: 99%
“…Even in four-strategy games experiments (Cason et al, 2010;Van Huyck et al, 1999), the concerned cycles are in the Euclidean plane. In the price dynamics cycle investigation, the price as a strategy is continuous; however, the theoretical expectation and experimental measurement are projected onto the Euclidean two-dimensional plane for verification (Cason et al, 2021)).…”
Section: Discussionmentioning
confidence: 99%
“…Game dynamics theory, which is based on evolutionary game theory, has been less developed over the last 50 years. In the past ten years, important progress has been made in the merging of theory and experiment (Cason et al, 2014;Wang et al, 2014;Xu et al, 2014;Cason et al, 2021). However, theoretical inferences and experimental measurements have failed to eliminate the constraints of twodimensional Euclidean space (e.g., the theoretical expectation is two-dimensional (Cason et al, 2010;Xu et al, 2014;Cason et al, 2014;Wang et al, 2014) or measured in two-dimensions (Cason et al, 2021)).…”
Section: The Backgroundmentioning
confidence: 99%
“…QRE could emerge as the long-run outcome of logit response dynamics (Alós-Ferrer and Netzer, 2010;Cason et al, 2021), as players form beliefs from observed history and choose stochastic best-responses. Instead, FRE could emerge as the long-run outcome if players favor actions that are frequent best-responses to the observed history, in a manner similar to probability matching (Vulkan, 2000).…”
Section: Frequent Response Equilibriummentioning
confidence: 99%